2020
DOI: 10.1080/19490976.2020.1794263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fecal microbiota transplantation in subjects with irritable bowel syndrome are mirrored by changes in gut microbiome

Abstract: Irritable bowel syndrome (IBS) is a common disorder of the lower gastrointestinal tract. The pathophysiology is far from settled, but a gut microbial dysbiosis is hypothesized to be a contributing factor. We earlier published a randomized double-blind placebo-controlled clinical trial on fecal microbiota transplantation (FMT) for IBS – the REFIT trial. The present data set describes the engraftment and includes participants from the study who received active FMT; 14 participants with effect of FMT ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 49 publications
1
21
0
Order By: Relevance
“… 13 On the other hand, Goll et al recently reported that responders to FMT had a trend of convergence toward donor microbiome profile after FMT while this trend was less clear for non-responders. 26 El-Salhy et al did not find any improvement in ‘dysbiosis index’ with FMT in IBS patients despite finding FMT was effective in improving IBS symptoms. 14 Our study was designed to detect the effect of antibiotic pretreatment on post-FMT bacterial engraftment and not the association between bacterial engraftment and clinical response.…”
Section: Discussionmentioning
confidence: 94%
“… 13 On the other hand, Goll et al recently reported that responders to FMT had a trend of convergence toward donor microbiome profile after FMT while this trend was less clear for non-responders. 26 El-Salhy et al did not find any improvement in ‘dysbiosis index’ with FMT in IBS patients despite finding FMT was effective in improving IBS symptoms. 14 Our study was designed to detect the effect of antibiotic pretreatment on post-FMT bacterial engraftment and not the association between bacterial engraftment and clinical response.…”
Section: Discussionmentioning
confidence: 94%
“…18,42,43 However, many studies have used autologous FMT as placebo treatment and hence the true effect of the donor derived allogenic FMT is difficult to distinguish. As we report no beneficial effects of increasing gut microbiome diversity and Goll et al- 44 reported response only in patients, that did not increase their diversity, based on microbiome data from a study of FMT treatment to IBS patients delivered through colonoscopy, 45 simply to increase gut microbiome diversity following FMT cannot be used as a marker of beneficial effects.…”
Section: Discussionmentioning
confidence: 44%
“…However, FMT only induced a transient relief for 3 months in accordance with Lahtinen's research, coinciding with the result of Johnsen's study ( 17 , 21 ). Interestingly, relatively long-term conversions of the composition of gut microbiota were also detected in their studies ( 21 , 29 ). It may attribute to the complex integrated effects of multiple factors.…”
Section: Discussionmentioning
confidence: 67%